2021
DOI: 10.1002/ar.24770
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology‐based investigation to explore the effect and mechanism of Erchen decoction against the nonalcoholic fatty liver disease

Abstract: This study aimed to uncover the potential mechanism of Erchen decoction (ECD) on the amelioration of nonalcoholic fatty liver disease (NAFLD). Network pharmacology and bioinformatics were used to determine the active components of ECD and its potential target in treating NAFLD. High fat diet (HFD)-induced NAFLD mice model was used. Liver tissues were stained with hematoxylin and eosin, and Oil Red O. Serum lipid profiles and hepatic inflammatory molecules in lipopolysaccharide (LPS)/Toll-like receptor-4 (TLR-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…We also found that the epididymal visceral adipose tissue had larger lipid droplets which is a sign of increased dampness in the body after high-fat diet feed. ECD is clinically used in China to treat obesity and hyperlipidemia by its dampness-reducing effects [12,13]. ECD has been also demonstrated to prevent highfat diet-induced metabolic disorders [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the epididymal visceral adipose tissue had larger lipid droplets which is a sign of increased dampness in the body after high-fat diet feed. ECD is clinically used in China to treat obesity and hyperlipidemia by its dampness-reducing effects [12,13]. ECD has been also demonstrated to prevent highfat diet-induced metabolic disorders [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Erchen decoction (ECD) is a common prescription in traditional Chinese medicine (TCM) to treat obesity and its related diseases [ 12 , 13 ]. ECD is composed of Pinellia ternata, tangerine peel, Poria cocos, and Glycyrrhiza uralensis.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription consists of Pinellia Ternata (BX) (250 g), Exocarpium Citri Rubrum (JH) (250 g), Poria Cocos (FL) (150 g), and Radix et Rhizoma Glycyrrhizae (GC) (75 g). Relevant studies have shown that ECD has a certain effect on treating metabolic diseases such as hyperlipidemia, diabetes, atherosclerosis, and metabolic syndrome [11][12][13], digestive diseases such as non-alcoholic fatty liver [14], and respiratory diseases [15]. Additionly, ECD can improve both the metabolic syndrome and mental symptoms of a psychopath with schizophrenia [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, network analysis played an important role in screening targets of liver disease. For example, the treatment study of Erchen decoction in nonalcoholic fatty liver disease (NAFLD) has shown that the interactions of active ingredients of Erchen decoction with 77 targets related to NAFLD mainly reduces inflammation’s stimulation of the liver through the TLR4 signaling pathway ( Liu et al, 2021 ). Xu et al (2021b) used the network pharmacological method to analyze the mechanism of schisandrol B in the treatment of CCl4-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%